Effect of Profitability (RoA) and Liquidity (CR) on Profit Growth in Companies Pharmaceutical Sector IDX - Dirjon Sitohang; Harlyn Siagian (Ekonomis: Journal of Economics and Business, 2021)
Profit growth is important for the sustainability of the company. At this particular time, covid-19 is a problem everywhere. So the pharmaceutical industry is being encouraged by the government to continue to build a good and more integrated structure. Profit growth can be analyzed using financial ratios. The financial ratios used in this study are liquidity, profitability, and company growth. This study used a purposive sampling technique. The research population used is pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) 2015-2019 with a total sample of 9 companies. The result of this study is that profitability has a positive relationship with profit growth and also has a significant effect. On the other hand, liquidity has a negative relationship with profit growth but is not significant. Simultaneously, profitability and liquidity have a significant positive relationship to profit growth.